Model Land Supply for Land Bank to House Application - Martin Roestamy (BESTUUR, 2020)
This study aimed to find out Land Bank's land supplies to provide land for affordable housing and establish community paradigm for ownership in which building separates from its property. The study was performed using a mixed methodology; namely informative where the primary legal material as a legal framework of housing construction is highlighted by considering legal research conducted with simple legal norms with attention to primary data such as land tenure, land availability, and the amount of housing backlogs that extended to help research. Quantitative data used as a measure of flaws in the application of drugs and legal framework, so that all legal resources can be supplemented with quantitative and qualitative data to find alternatives and open access for LIPs' houses.   Keywords: Land Supply; Land Bank; Affordable Housing.